Optimising fertigation of hydroponically grown sowthistle (Sonchus oleraceus L.): The impact of the nitrogen source and supply concentration - Antonios Chrysargyris; Nikolaos Tzortzakis (Agricultural Water Management, 2023)
The efficient use of water and nutrients in leafy vegetable crops can be improved by effective water management, whereas the form of the supplied nitrogen may affect their quality and productivity. Sowthistle (Sonchus oleraceus L.), a widespread weed collected and consumed as a wild vegetable in the past, currently attracts a high interest for commercial cultivation due to its high nutritional value. The present study evaluated the effects of different nitrogen concentrations: N50: 50 mg L−1; (N 3.6 mmol L−1), N100: 100 mg L−1; (N 7.1 mmol L−1), N200: 200 mg L−1; (N 14.3 mmol L−1), and N300: 300 mg L−1; (N 21.4 mmol L−1) and different ammonium/total-N ratios (Nr: 0.01, 0.05, 0.10, 0.15) on growth, physiological parameters, antioxidant capacity and nutrient accumulation in the different plant parts of sowthistle, grown in Nutrient Film Technique hydroponic system. Total N was ammonium N plus nitrate N. Plant growth, total phenols, and antioxidant capacity were higher at the two intermediate N concentrations, whereas flavonoid and nitrogen content, as well as irrigation water productivity increased only with 200 mg N L−1 (N 14.3 mmol L−1), compared to the other three N concentrations. The accumulation of nitrogen in leaves and roots was lower, while leaf stomatal conductance was enhanced by increased N concentrations in the nutrient solution. Higher Nr ratios than ≥ 0.05 decreased plant dry matter, total phenols, flavonoids, and antioxidant capacity in leaf extracts, and negatively affected nitrogen translocation from roots to leaves. Sowthistle plants treated with a Nr of 0.05 exhibited a less intense oxidative stress, with decreased lipid peroxidation and hydrogen peroxide production, and increased superoxide dismutase and catalase activities, compared to those treated with higher Nr ratios. Increased Nr resulted in the accumulation of phosphorus and magnesium in leaves while the highest irrigation water productivity was obtained in plants grown with a Nr of 0.05. In conclusion, to increase yield, nutritional value and efficiency of water and nitrogen use in sowthistle grown in closed hydroponic systems, a N concentration of 200 mg L−1 of N (N 14.3 mmol L−1) and a Nr of 0.05 are suggested.